2015
DOI: 10.7326/l15-5049-3
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Hepatocellular Carcinoma in Chronic Liver Disease

Abstract: Management of the Unilateral Shoulder Impingement SyndromeTO THE EDITOR: On the surface, Rhon and colleagues' thoughtful study (1) shows the effectiveness of subacromial corticosteroid injection and manual physical therapy (MPT) to treat the shoulder impingement syndrome (SIS). However, several factors complicate the comparison of MPT with medical intervention and perhaps limit this study's otherwise valuable contribution.First, the manual therapy approach used was welldescribed in Rhon and colleagues' study (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…19,20 A single Chinese randomised controlled trial did demonstrate a survival benefit in those screened when compared to the control group. 21 However, this study has been criticised due to its design and subsequent analysis, 22 and it is likely to have overestimated the benefits of surveillance due to these concerns.…”
Section: Possible Benefits Of Surveillancementioning
confidence: 99%
“…19,20 A single Chinese randomised controlled trial did demonstrate a survival benefit in those screened when compared to the control group. 21 However, this study has been criticised due to its design and subsequent analysis, 22 and it is likely to have overestimated the benefits of surveillance due to these concerns.…”
Section: Possible Benefits Of Surveillancementioning
confidence: 99%
“…Although to our knowledge there are few data regarding the true effectiveness of HCC screening, a recent meta-analysis found that HCC surveillance is associated with significantly improved early-stage detection (odds ratio [OR], 2.08; 95% confidence interval [95% CI], 1.80-2.37), curative treatment rates (OR, 2.24; 95% CI, 1.99-2.52), and prolonged survival (OR, 1.90; 95% CI, 1.67-2.17), even in studies adjusted for lead time bias. 5 It is also important to emphasize that a prerequisite for effective screening is the identification of an appropriate population, an area that should be actively investigated as SVR becomes more frequent. As such, further studies need to be performed that identify those individuals achieving SVR who remain at highest risk of developing HCC to select those who would most benefit from screening.…”
Section: Funding Supportmentioning
confidence: 99%
“…However, a systematic review of the benefits-to-harm ratio of HCC screening in patients with liver disease confirmed the lack of evidence of a benefit for patients. 5 Long raw data analyses of observational studies have repeatedly shown that nonscreened patients die at an older age than screened patients (lead time and length time bias) and, among the 3 randomized controlled trials that to my knowledge are the only ones currently available, only one, from China, is positive but has several major flaws. [6][7][8] In a large European cohort, the population-attributable fraction for tobacco use in patients with HCC was 47.6%, which is more than twice the population-attributable fraction of the second most attributed risk factor (HCV at 20.9%).…”
mentioning
confidence: 99%
“…Both the AASLD and EASL-EORTC guidelines recommend 6 monthly surveillance using abdominal ultrasonography in high risk patients, although the definition of which patients are considered high risk varied [10,11] Interestingly, a systematic review of the benefits and harms of HCC screening in patients with chronic liver disease found only poor quality evidence to support the benefits of screening. Of the two randomised controlled trials reviewed, only one demonstrated a survival benefit (ultrasound screening) and one found no difference in all-cause mortality (alpha-feto protein screening) [12] . Improvements in surgical technique and perioperative care have led to a fall in the morbidity and mortality of liver resection over the last two decades.…”
Section: Surgical Resectionmentioning
confidence: 99%